Elektroniczne zarządzanie dokumentacją jako przykład informatyzacji działalności administracji publicznej - Hic, Piotr; Nowakowski, Rafał (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
In this article both of authors present definition and assumption of “Elektroniczne Zarządzanie Dokumentacją” ICT system (Electronic Management of Documentation). First part of the article describes legal definition of EZD as well as tasks, which are anticipated by this ICT system. Second part of the article sets out implementation of EZD to local government administration, including technical, financial and organizational site of the implementation
Keywords: administracja elektroniczna; elektroniczne zarządzanie dokumentacją; zarządzanie; administracja publiczna; informatyzacja administracji publicznej; informatyzacja